Designing Consent Processes for Research With Older Adults Who May Lack Decisional Capacity: A Guide for Investigators. - Largent, Emily A.; Morain, Stephanie R.; Karlawish, Jason (Journal of the American Geriatrics Society, 2026)
Securing a participant's voluntary, informed consent is widely acknowledged as a requirement of ethical research. Yet, challenges can arise, particularly when a researcher seeks to enroll older adults who may lack the capacity to consent to research participation due to cognitive impairment. To address this challenge, this article outlines a nine‐step framework for designing consent processes: (1) identify the participants in the study and assess whether some or all might reasonably be expected to lack decisional capacity; (2) determine whether enrolling participants who lack decisional capacity is justifiable; (3) determine whether informed consent is needed for some or all research procedures; if consent is required, (4) prepare the information that will be provided to prospective participants; (5) make both the information and the consent process accessible; (6) specify how prospective participants' decisional capacity will be assessed; (7) specify how surrogates will be identified and contacted when prospective participants are determined to lack decisional capacity; (8) determine how to involve prospective participants who lack decisional capacity in the decision‐making process, such as through assent or dissent; and as appropriate, (9) consider how capacity and consent might change across the duration of the study. This framework can help researchers anticipate and address common challenges and ensure they fulfill ethical and regulatory obligations. Applications of this framework include writing the human subjects portion of grant applications, preparing protocols for submission to an Institutional Review Board, and informing research practice.